Vacationland ebook A novel. - Mitchell Moore, Meg (2022)
A Sarah Selects Book Club Pick! "As sophisticated and delicious as lobster bisque." —Amanda Eyre Ward, New York Times bestselling author A shimmering summer read set in Maine about family secrets, marriage, motherhood, and privilege, from the bestselling author of Two Truths and a Lie and The Islanders. Louisa has come to her parents' house in Maine this summer with her three kids, a barely written book that has a looming deadline, and a trunkful of resentment. Louisa is hoping the crisp breeze will blow away her irritation for her life choices and replace it with enthusiasm for both her family and her writing. But all isn't well in Maine. Louisa's father, a retired judge and pillar of the community, is suffering from Alzheimer's. Louisa's mother is alternately pretending everything is fine and not pretending at all. And one of Louisa's children happens upon a very confusing and heartfelt letter referring to something Louisa doesn't think her father could possibly have done. Louisa's not the only one searching for something in Maine this summer. Kristie took the Greyhound bus from Pennsylvania with the $761 left in her bank account and a whole lot of emotional baggage. She has a past she's trying to outrun, a secret she's trying to unpack, and a new boyfriend who's so impossibly kind she can't figure out what she did to deserve him. As June turns to July turns to August, secrets will be unearthed, betrayals will come to light, and both Louisa and Kristie will ask themselves what they are owed and what they owe others. Both a delicious summer read and a compelling portrayal of family, responsibility, ambition, and loss, Vacationland is Meg Mitchell Moore at her best.